Hepatoid adenocarcinoma of the stomach: CT findings - Yang, Qian; Liu, Yulin; Zhang, Shuixia (Frontiers in Oncology, 2023)
Objective To analyze the CT findings of hepatoid adenocarcinoma of the stomach (HAS) and improve the diagnosis accuracy of this condition. Methods The CT images of 22 pathologically confirmed HAS patients were analyzed retrospectively. We investigated the location of lesions, morphology, enhancement features, area of invasion into surrounding organs, lymph node metastasis, and venous tumor thrombus. Results Among the 22 patients (17 men and 5 women, the mean age was 61.41 ± 9.83 years ranging from 36 to 80 years) with HAS; the morphology of tumors included mass (n = 5), focal ulcer (n = 7), and infiltrating ulcer (n = 10). Extraserous fat was invaded in 12 cases. Enhancement scans showed continuous enhancement in all cases. The CT values of unenhanced scan, the arterial phase, and the portal venous phase are 30.36 ± 6.46, 60.91 ± 17.80, and 75.64 ± 22.09 (Hounsfield Unit, HU), respectively. In six cases, the tumor infiltrated the surrounding organs: liver (n = 1), pancreas (n = 2), and both liver and pancreas (n = 3). In 16 out of 22 patients (72.3%), suspicious lymph node metastasis at CT imaging has then been confirmed by pathological specimens. Intrahepatic metastasis was found in 14 cases. Seven patients had venous tumor thrombus: three patients developed tumor thrombus in the main trunk and intrahepatic branches of the portal vein and two patients in the portal vein, splenic vein, and superior mesenteric vein simultaneously. Conclusion The CT scans of HAS often show a thickened gastric wall and infiltrating ulceration. Infiltration into extraserosal fat is often seen. Enhancement scans show a continuous and progressive enhancement of lesions. Lymph node metastasis, intrahepatic metastasis, and portal vein tumor thrombus are common in HAS patients.